Cyst‐Theca Relationship and Phylogenetic Position of Impagidinium caspienense Incubated from Caspian Sea Surface Sediments: Relation to Gonyaulax baltica and Evidence for Heterospory within Gonyaulacoid Dinoflagellates. (11th May 2017) - Mertens, Kenneth N.; Takano, Yoshihito; Gu, Haifeng; Bagheri, Siamak; Pospelova, Vera; Pieńkowski, Anna J.; Leroy, Suzanne A. G.; Matsuoka, Kazumi
Abstract: We investigate the cyst‐theca relationship of Impagidinium caspienense . Through an incubation experiment, we succeeded in examining the motile stage. Additional molecular analysis of single‐cyst PCR (LSU and SSU rDNA) reveal that the cyst is related to the species Gonyaulax baltica Ellegaard et al. (2002 ). The ability of this species to belong to two types of cyst‐based genera (spiniferate and impagidinioid) suggests that environmental (particularly salinity) and not genetic factors explain the formation of both morphotypes by G. baltica, which provides evidence for heterospory in this species. The affiliation to G. baltica demonstrates that I. caspienense is not endemic to the Caspian Sea. The phylogenetic position of several other gonyaulacoid species is also documented: Impagidinium pallidum, Ataxiodinium choane, Pyxidinopsis psilata, Spiniferites belerius, and Spiniferites ramosus . The LSU and SSU rDNA based phylogenies suggest that the genera Impagidinium and Spiniferites are not monophyletic, and that P. psilata and A. choane are close to Gonyaulax verior and Gonyaulax polygramma, respectively. In addition, this study accentuates the importance of cyst morphology in the classification of the Gonyaulacales.